Nuts: multi-purpose and profitable - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Most nuts are highly nutritious and some have a high sale value. Cashew and macadamia are much in demand for export while other kinds of nuts are produced more locally and may be unknown outside a particular region. Some of these also have the...